The Occurrence, Hemolytic, Cytotoxic Activity and Antibiotic Susceptibility of Aeromonas hydrophila Isolated from Fish Samples in Baghdad - Alzainy, Zainab Aun Ali (The Iraqi Journal of Veterinary Medicine, 2011)
In this study a total of 60 samples of lived fishes (common carp) and frozen fishes were collected from 15 local markets in Baghdad city ,for isolation of Aeromonas hydrophila to determine the hemolytic ,cytotoxic activity of the isolates and their antibiotic susceptibility , 65% of our samples were found to be positive for Aeromonas hydrophila isolation 76.6% were in life fish samples and 53.3% in frozen fish 94.87% exhibited α and β hemolysis, 100% of life fish isolates show β hemolysis while frozen fish isolates show 85.7% β hemolysis and 14.3% α hemolysis , 97.43% of isolates show cytotoxic effect on Vero cells the highest frequency occur in the isolates of life fish group 60.50% , all isolates were 100% resistant to pencillin , ampicillin , Cloxacillin and Bacitracin in sensitivity test , and the resistance to other antibiotics appear to oxytetracycline 56.5% ,tetracycline 33.4% ,cephoxetin 30.8% , chloramphinicol and kanamycin 28.2% , at last the isolates show resistant to streptomycin and rifampicin in 23.1% and 15.4% respectively. These results demonstrated the presence of virulent food borne Aeromonas hydrophila in fish with multiple antibiotic resistance in Baghdad markets.